HAMBATAN-HAMBATAN BELAJAR SISWA PADA MATA PELAJARAN MEMBUAT POLA (PATTERN MAKING) DENGAN TEKNIK KONSTRUKSI DI SMK NEGERI 1 IV ANGKEK KAB. AGAM - Ningsih, Yani Dwi; Idrus, Yenni; Izwerni, Izwerni (Journal of Home Economics and Tourism, 2012)
This study originated from the fact that occurred in SMK Negeri 1 IV Angkek Agam District, where many students are not able to make the patterns correctly. This study aims to find out how big the obstacles faced by students in taking body size and pattern making on subjects making patterns with construction techniques.Population and samples in this study were students of class XI dressmaking subjects totaling 24 people. Data collection in this study conducted by distributing questionnaires or questionnaires totaled 50 item. Data analysis technique used is the percentage of technique and performance levels. The results show that constraints on the subjects students create patterns with construction techniques in SMKN 1 Agam District IV Angkek still pretty. This is evident from the level of achievement of the measure gain of 76.77% and 78.84% for pattern making, this means that students still find obstacles in subjects making patterns. Expected results of this study for teachers and students.